Evaluation and quality assessment of defatted microalgae meal of Chlorella as an alternative food ingredient in cookies. Issue 2 (24th October 2018) - Sahni, Prashant; Sharma, Savita; Singh, Baljit
Abstract : Purpose: Meal left after extraction of microalgae functional compounds is not finding its application in food. Hence, present study was aimed for the development of the cookies supplemented with meal of microalgae Chlorella sp . (Abca-17) obtained after solvent extraction of chlorophyll. Design/methodology/approach: Cookies were prepared by substituting refined wheat flour (RWF) with microalgae meal (MM) at incorporation levels of 3, 6, 9 and 12 per cent. The effect of replacement of RWF with MM was analyzed on the pasting properties of the flour blends and physical, chemical, sensory and textural characteristics of the cookies. Findings: MM exhibited high water and oil absorption capacity of 0.8 g/g and 1.2 g/g, respectively. Weight and thickness of the cookies increased, whereas the diameter, spread ratio and spread factor decreased with the increased proportion of meal in flour blends. The moisture and ash content (0.8-2.0 per cent) of the cookies increased, whereas fat content showed no pronounced variation. Sensory evaluation of cookies revealed no significant difference at 6 per cent level of incorporation and further supplementation resulted in dark colour and increased hardness. Texture profile analysis of cookies also revealed that the peak positive force for breaking the cookies increased (3115.6-7372.1 N) with increase in the level of incorporation of meal. Practical implications: MM can be used in the development of the cookies at level of incorporation of 6 per cent and presents novice approach for utilization of bioprocessing waste. Originality/value: The present study is a pioneer effort in demonstration of utilization of MM as alternate food ingredient. MM of Chlorella sp . (Abca-17) was characterized as food ingredient using physicochemical analysis and model food system using cookies.